(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article examines the incidence of precancerous ovarian pathologies in women of reproductive age in the Bukhara region. The data were analyzed on the basis of surgical biopsy materials for 2021, obtained by the Bukhara Regional Bureau of Pathology. Precancerous ovarian pathologies were examined in 44 women of reproductive age. As a result of examination, ovarian cysts were detected in 44 cases, in 26 cases (60%) in women aged 40-50 years, in 15 cases (34%) in women aged 30-40 years and in 3 cases (6.8% ) in women aged 20-30 years.